Impact of direct exchange coupling via the insulator on the magnetic tunnel junction based molecular spintronics devices with competing molecule induced inter-electrode coupling - Hayden Brown; Andrew Grizzle; Christopher D’Angelo; Bishnu R. Dahal; Pawan Tyagi (AIP Advances, 2021)
The magnetic tunnel junction (MTJ) based molecular spintronics device (MTJMSD) approach is suitable for mass production. This approach provides solutions to fabrication difficulties related to reliably connecting molecular device elements to the ferromagnets (FMs). To producing MTJMSD, the molecular channels are bridged across the insulator of an MTJ testbed with exposed side edges. In an MTJMSD, two FMs are simultaneously connected by an insulator film and the molecular channels along the exposed sides. In our prior experimental studies, we observed that molecules could produce strong coupling between ferromagnets in the presence of the competing coupling via an insulator. In this paper, our Monte Carlo Simulation (MCS) was used to study the impact of coupling variation via insulator (a.k.a. Ji) on the magnetic properties of an MTJMSD. We studied the effect of Ji while varying the molecule induced antiferromagnetic exchange coupling. The ferromagnetic or antiferromagnetic nature and magnitude of Ji determined the resultant effect. Antiferromagnetic Ji enhanced the pre-existing antiferromagnetic molecular coupling effect. Ferromagnetic Ji competed with the opposite nature of antiferromagnetic molecular coupling. Our MCS may help to understand the impact of insulator thickness and defects on the molecular spintronics device performance and design process.